Economic resilience and tourism destinations: eco and cultural responses to turbulence contexts in coastal areas - Porter, Julie (2012)
Since 2007, the economic recession has had a significant impact on European regional economies, particularly the tourism sector. The combination of increasing oil prices and the reduction of purchasing power created a vast reduction of both foreign and domestic tourists, as well as lower spend from tourists, across Europe. Destinations focusing on standardised products were especially affected. This paper will stress the role of innovative coastal tourism activities to overcome the tensions caused by economic turbulence. Due to the unequal distribution of tourism across the EU, locations where tourism is socioeconomically significant to the region will be compared, using the cases of coastal tourism in Wales (UK), Algarve (Portugal), and Province of Huelva in Andalusia (Spain). Data from these regions was collected through the Atlantic Area KIMERAA project. For each case study, semi-structured interviews were conducted with SMEs, policymakers and Universities. These interviews, and further secondary source analysis, provided evidence that these regions were recovering from the economic resilience shock through diversifying their tourism markets particularly focusing on ecotourism and cultural tourism.